An Analysis of Theoretical Review of Generative Grammar in Contemporary Linguistics - Helmi, Rahil; Ghina, Inas; Destari, Dinda; Bhat, Sameer Rashid (LET: Linguistics, Literature and English Teaching Journal, 2025)
This article presents a theoretical analysis of Generative Grammar and its relevance in contemporary linguistics. The discussion begins with an overview of the origins of Generative Grammar, particularly the contributions of Noam Chomsky, who introduced the idea that language is a mental capacity governed by an internal system of rules known as Universal Grammar. Utilizing a qualitative analytical method, the article synthesizes and compares primary theoretical contributions and critiques from various linguistic schools to assess the current status and applicability of Generative Grammar. The analysis reveals that Generative Grammar continues to play an important role in linguistic theory, especially in understanding syntactic phenomena and language acquisition.